Penultimate Approximation for Hill's Estimator - S. Cheng; L.F.M. de Haan (Tinbergen Institute, 1999)
We prove that the probability distribution of Hill's estimator can be betterapproximated by a series of appropriate gamma distributions than by the limitingnormal distribution.
Keywords: 330; Schätztheorie; Theorie